Gradual Replacement of Soybean Meal with Brewer’s Yeast in Fingerling Nile Tilapia (Oreochromis niloticus) Diet, Resulting in a Polynomial Growth Pattern, Independent of Whether Reared in a Biofloc or Clear-Water System - Nguyen Huu Yen Nhi; Trinh Thi Lan; Kartik Baruah; Torbjörn Lundh; Anders Kiessling (Aquaculture Journal, 2024)
A 60-day feeding experiment was conducted to examine whether (i) soybean meal (SBM) protein in the diet of Nile tilapia (Oreochromis niloticus) can be replaced with protein from spent brewer’s yeast (SBY); (ii) co-rearing with biofloc alters fish growth, feed conversion and protein efficiency compared with rearing in clear water; and (iii) accumulated protein quantity and quality in biofloc acts as a possible feed source for the fish in periods of low feed intake. The fish were reared in either a bio-recirculating aquaculture system (Bio-RAS) or a clear-water RAS (Cw-RAS). In Bio-RAS, the mechanical and biological filters used in Cw-RAS were replaced with an open bioreactor that delivered heterotrophic-based biofloc to the rearing tanks and also acted as a sedimentation trap for effluent water before recirculating it back into the rearing unit. The fish were fed four iso-nitrogenous and iso-energetic diets (~28% crude protein, ~19 MJ kg−1 gross energy) in which SBM protein was replaced with increasing levels of SBY, with triplicate tanks per inclusion level. The results revealed that average fish growth was greater in a biofloc environment compared with clear water and also greater at higher inclusion levels of SBY. However, in both rearing environments, fish growth displayed a second-degree polynomial distribution with increasing SBY inclusion level, with a peak between 30% and 60% inclusion. Fish in the biofloc environment showed better feed conversion ratio and protein retention, likely through ingesting both given feed and biofloc. Biofloc contained a significant amount of accumulated protein with a high biological profile, thereby constituting a possible feed reserve for the fish. A conclusion underlined by the apparent improved feed conversion of Bio-RAS reared fish, where that ingestion of biofloc will reduce the need for external feed per unit growth.